2022
DOI: 10.18632/aging.204341
|View full text |Cite
|
Sign up to set email alerts
|

Identify miRNA-mRNA regulation pairs to explore potential pathogenesis of lung adenocarcinoma

Abstract: Purpose: MicroRNA (miRNA) function via base-pairing with complementary sequences within mRNA molecules. This study aims to identify critical miRNA-mRNA regulation pairs contributing to lung adenocarcinoma (LUAD) pathogenesis. Patients and methods: MiRNA and mRNA microarray and RNA-sequencing datasets were downloaded from gene expression omnibus (GEO) and the cancer genome atlas (TCGA) databases. Differential miRNAs (DE-miRNAs) and mRNAs (DE-mRNAs) were screened by the GEO2R tool and R packages. DAVID, DIANA, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…We veri ed this nding in samples from 20 pairs of patients and a new miRNA sequence, miR-1246b has caught our attention. The AUC for the diagnosis of benign and malignant pulmonary nodules was only 0.741, which may be related to our small sample size; Furthermore, previous studies have also found that the diagnostic performance of multiple miRNAs is higher than that of a single miRNA in tumors [38,39]. Therefore, a follow-up study should be carried out to expand the sample, simultaneously, a combination with other miRNAs may be considered.…”
Section: Discussionmentioning
confidence: 82%
“…We veri ed this nding in samples from 20 pairs of patients and a new miRNA sequence, miR-1246b has caught our attention. The AUC for the diagnosis of benign and malignant pulmonary nodules was only 0.741, which may be related to our small sample size; Furthermore, previous studies have also found that the diagnostic performance of multiple miRNAs is higher than that of a single miRNA in tumors [38,39]. Therefore, a follow-up study should be carried out to expand the sample, simultaneously, a combination with other miRNAs may be considered.…”
Section: Discussionmentioning
confidence: 82%
“…The AUC for miR-1246b in the diagnosis of benign and malignant pulmonary nodules was only 0.743, which may be related to our small sample size. Furthermore, previous studies have found that the diagnostic performance of multiple miRNAs is higher than that of a single miRNA in tumors [ 38 , 39 ]. Therefore, a follow-up study should be carried out to expand the sample size; a combination with other miRNAs may also be considered.…”
Section: Discussionmentioning
confidence: 99%
“… 14 miRNA takes part in many biological processes of metabolism, cell differentiation, apoptosis, and disease control, involving multiple systems, including respiratory system, cardiovascular system, nervous system, and hematopoietic system. 15 Excessive studies have confirmed the correlation of miRNA with the growth and development of lung, as well as onset, development, and outcome of pulmonary fibrosis, pneumonia, lung cancer, chronic obstructive pulmonary disease, and so on. 16 , 17 Lin et al 8 demonstrated that miR-24 inhibited inflammatory response in neonatal rats with lipopolysaccharide-induced acute lung injury by targeting NLRP3.…”
Section: Discussionmentioning
confidence: 99%